(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, we will highlight aspects related to the use of the linden plant in plant breeding based on the study of the biology of flowering, structure, development and seed productivity of the linden plant in the climatic conditions of the city of Fergana. From this point of view, the main reproductive organ of the linden is a flower, the structure and development of the seed bud inside the seed box located in the center, the study of the formation of the maternal gametaphyte will not only improve the knowledge of young scientists, but also carry out seed production and breeding work, and has practical significance.